2021
DOI: 10.24869/spsih.2020.285
|View full text |Cite
|
Sign up to set email alerts
|

Protective and Risk Factors in Adjusting to the Covid-19 Pandemic in Croatia

Abstract: Poliklinika za zaštitu djece i mladih Grada Zagreba; 2 Gradski ured za socijalnu zaštitu i osobe s invaliditetom,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…All these factors seem to apply to the current COVID-19 pandemic. Previous research has also indicated that psychological reactions during epidemics are likely to be influenced by personal dispositions, individual coping strategies, and one's perceived control over the situation, and social support which is in line with most stress theories [3,8,9]. Coping style may play an important role in mediating psychological symptoms after stressful or traumatic events [10,11].…”
Section: Introductionmentioning
confidence: 60%
“…All these factors seem to apply to the current COVID-19 pandemic. Previous research has also indicated that psychological reactions during epidemics are likely to be influenced by personal dispositions, individual coping strategies, and one's perceived control over the situation, and social support which is in line with most stress theories [3,8,9]. Coping style may play an important role in mediating psychological symptoms after stressful or traumatic events [10,11].…”
Section: Introductionmentioning
confidence: 60%
“…Furthermore, most participants did not have a significant fear of COVID-19 in the first assessment, which is consistent with the results of other studies with persons with SMI (Muruganandam et al, 2020), although the fear of COVID-19 intensified over the time. According to published studies, the fear of COVID-19 disease seems to be similar or a bit lower compared to the general population (Buljan Flander et al, 2020; Roy et al, 2020; Wolf et al, 2020). The explanation for this may be a greater focus to the internal then external reality in persons with SMI and the existence of social isolation in patients due to the mental illness itself (Slade, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our results both confirm some previous findings and add further novel findings to the literature. Previous studies have indicated that gender (Buljan Flander et al, 2020;Dryhurst et al, 2020;Galasso et al, 2020;Gerhold, 2020;Szabo et al, 2020;Alsharawy et al, 2021;Rana et al, 2021), age (Buljan Flander et al, 2020;Galasso et al, 2020;Gerhold, 2020;Szabo et al, 2020;Bechard et al, 2021;Laires et al, 2021), chronic conditions (Laires et al, 2021;Ricotta et al, 2021), and region (Gerhold, 2020;Parsons Leigh et al, 2020) can explain some of the variability in different COVID-19 threat beliefs. In line with the previous findings, these variables were significant predictors of COVID-19 threat beliefs in the first step of our regression analyses, accounting for 4.4% of the variance, with age and chronic conditions remaining significant predictors in the last step.…”
Section: Discussionmentioning
confidence: 99%
“…We examined how individual differences in demographics, personality, and other related beliefs contribute to COVID-19 threat beliefs. Based on previous findings (Buljan Flander et al, 2020;Dryhurst et al, 2020;Galasso et al, 2020;Gerhold, 2020;Szabo et al, 2020;Alsharawy et al, 2021;Bechard et al, 2021;Laires et al, 2021;Rana et al, 2021;Ricotta et al, 2021), we expected women, older people, and people with chronic diseases to believe that COVID-19 poses more risk, and we expected regional differences in beliefs about COVID-19 risks (Gerhold, 2020;Parsons Leigh et al, 2020). Furthermore, we expected that COVID-19 threat beliefs will be related to personality factors as operationalized using the HEXACO model (Lazarević et al, 2021;Zettler et al, 2022).…”
Section: This Studymentioning
confidence: 98%
See 1 more Smart Citation